Exploring the correlations of lung ultrasound with delirium and other clinical outcomes in older patients with respiratory failure admitted in acute geriatric units (ECO-AGE): protocol for a multicentre, prospective, observational study from the GRETA Group (Gruppo di Ricerca in Ecografia Toracica nell’Anziano) of the Italian Society of Gerontology and Geriatrics (SIGG) - Andrea Ticinesi; Fulvio Lauretani; Antonio Nouvenne; Tiziana Meschi; Giuseppe Bellelli; Andrea Ungar; Marcello Maggio; Simone Scarlata; Raffaele Antonelli Incalzi; Fabio Monzani; Carmine Siniscalchi; Chukwuma Okoye; et al. (BMJ Open, 2025)
Introduction Point-of-care lung ultrasound (LUS) can assist in diagnosing acute respiratory diseases for its high accuracy and immediate availability at the bedside, including older patients with frailty. Delirium represents a frequent complication of hospitalisation in this setting, frequently triggered by acute respiratory diseases. LUS may therefore help identify individuals at risk of delirium, but the association between LUS abnormalities and delirium remains unexplored.Methods and analysis This study is a prospective, observational, multicentre study, with the main objective of assessing the correlation between LUS abnormalities and incident delirium during hospitalisation (primary outcome). The secondary objectives are to assess correlations between lung and diaphragm ultrasound parameters and clinical outcomes including duration of delirium, severity of respiratory failure and mortality. 480 patients aged ≥65 years old, urgently hospitalised after an emergency department visit for acute respiratory complaints, will be recruited in eleven acute geriatric wards located in eight teaching hospitals across Italy. LUS examinations will be performed by skilled clinicians prior to treatment whenever feasible, and in any case within 48 hours from admission. They will also undergo comprehensive geriatric assessment, and daily delirium assessment through the 4-AT tool. The association between LUS abnormalities, related parameters (LUS score, Pleural Effusion Score) and outcomes will be assessed by linear and logistic regression models.Ethics and dissemination Ethics Committee approval of the coordinating centre (Comitato Etico Territoriale Lombardia 3, reference ID 4369_20.03.2024_M) and collaborative centres has been obtained. All participants will provide written informed consent. Study results will be publicly available following peer-reviewed publication in international scientific journals.Trial registration number NCT06670118.